Evaluation of the antibacterial activity of Zea mays Linn. (Fam. Poaceae) husk extracts - Felipe, Kaye Angelique T.​; Llagas, Julia Patricia B.​; Xu, Abigail S.​; Gutierrez, Margarita M.​ (Manila College of Pharmacy, University of the Philippines, 2019)
In light of the rapid development of antimicrobial resistance, the discovery of new sources of antibacterials remains imperative. In the Philippines, one of the top-produced crops is corn (Zea mays). While kernels are edible and useful, the husk is often simply discarded. Corn silk, and husk from other plants in the Poaceae family, have already been found to possess antibacterial properties, but limited studies have been conducted on corn husk. In this study, the antibacterial activity of corn husk was determined, wherein hot and cold methanolic crude extracts, as well as aqueous, chloroform, and petroleum ether extract fractions of corn husk were tested using agar disk diffusion assay against three grampositive (Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus aureus) and one gram-negative (Escherichia coli) bacteria. Positive treatments, namely hot crude extract and aqueous fraction, were subsequently subjected to broth microdilution assay and contact bioautography against the four bacteria. Comparison of the zones of inhibition of hot crude extract (1.75 mg) and aqueous fraction (3.5 mg) with gentamicin (10 ug) shows that these treatments, while possessing antibacterial properties, are still considerably less potent than gentamicin at the tested concentrations. The minimum inhibitory concentrations for each of the four bacteria were determined for the hot crude extract, but was inconclusive for the aqueous fraction. Contact bioautography also showed no zones of inhibition for either treatment. Phytochemical screening revealed that alkaloids were present in these extracts, but not in the extracts that produced no bacterial inhibition, suggesting that alkaloids may be responsible for the antibacterial activity of corn husk.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, May 2019.
Keywords: Corn; Plant extracts; Antibacterial Activity